The implications of urban shrinkage for the budgets of Polish cities - Wichowska, Anna (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
Contemporary demographic processes involving the decline and aging of the population and the accompanying economic crisis in many cities around the world are referred to as shrinking. The causes and effects of this phenomenon are still insufficiently explained. The article investigates the financial effects of shrinking on the budgets of Polish cities. The article aims to indicate how the loss of inhabitants may affect the city’s economy, and thus the city’s budget, and to identify and assess differences between selected budget categories in shrinking cities and in those cities that have not experienced the problem of depopulation. First, a literature review was conducted, followed by a financial analysis of the budgets of shrinking cities, which was supplemented with a comparative analysis of the selected revenues and expenditures of budgets of cities that were not undergoing the shrinking process. The research period covered the years 2018–2022. As the analyses show, the way in which cities’ demographic problems impact their financial situation occurs through the economy, the condition of which in the era of knowledge-based economies depends on human capital resources. The financial analysis of selected budget indicators allowed us to conclude that shrinking cities had much lower budget revenues per capita, lower revenue independence, and lower budget expenditures. The opposite situation was observed in the case of expenditure on benefits for natural persons, the higher level of which in shrinking cities confirmed the need for greater involvement of cities in financing social policy.